The challenge of effectiveness - Pastore, Baldasare (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
This paper deals with the question regarding the crisis of the effectiveness of human and fundamental rights. This is a challenge that requires commitment, vigilance, shared liability. Rights are an indispensable tool for expressing the value of dignity that is linked to vulnerability as a common human condition. Rights are a type of social practice aimed at their implementation and concretization. It is made up of principles, rules, institutions, procedures, attitudes, acts of interpretation. This practice plays an important role in countering and eliminating the situations that produce violations concerning the subjects in their multiple differences and specific existences.
Keywords: rights; social practice; human dignity; effectiveness; concretization